2024
DOI: 10.3390/bioengineering11030219
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Synergy of Multi-Modal Data and AI Technologies in Medical Diagnosis

Xi Xu,
Jianqiang Li,
Zhichao Zhu
et al.

Abstract: Disease diagnosis represents a critical and arduous endeavor within the medical field. Artificial intelligence (AI) techniques, spanning from machine learning and deep learning to large model paradigms, stand poised to significantly augment physicians in rendering more evidence-based decisions, thus presenting a pioneering solution for clinical practice. Traditionally, the amalgamation of diverse medical data modalities (e.g., image, text, speech, genetic data, physiological signals) is imperative to facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 172 publications
0
1
0
Order By: Relevance
“…Challenges remain in standardizing methodologies and ensuring robust validation across diverse surgical contexts to optimize the integration of these technologies into clinical practice effectively. Machine learning and AI technology excel conventional methods in handling and processing large, high-dimensional data, integrating diverse types like imaging and clinical notes for a holistic analysis of patients who are subjected to surg ery Efficacy of machine learning algorithms versus conventional assessment techniques in predicting postoperative complications i n general surgery comprehensive literature review to estimate post-surgical risks (Zitnik et al, 2019) (Xu et al, 2024). Stam and colleagues' (2022) systematic research revealed that AI exceeds traditional approaches regarding accuracy in predicting postoperative complications since it can identify patterns missed by conventional methods.…”
Section: Kuo Et Al (2017)mentioning
confidence: 99%
“…Challenges remain in standardizing methodologies and ensuring robust validation across diverse surgical contexts to optimize the integration of these technologies into clinical practice effectively. Machine learning and AI technology excel conventional methods in handling and processing large, high-dimensional data, integrating diverse types like imaging and clinical notes for a holistic analysis of patients who are subjected to surg ery Efficacy of machine learning algorithms versus conventional assessment techniques in predicting postoperative complications i n general surgery comprehensive literature review to estimate post-surgical risks (Zitnik et al, 2019) (Xu et al, 2024). Stam and colleagues' (2022) systematic research revealed that AI exceeds traditional approaches regarding accuracy in predicting postoperative complications since it can identify patterns missed by conventional methods.…”
Section: Kuo Et Al (2017)mentioning
confidence: 99%